Rancang Bangun Aplikasi Pembelajaran Bahasa Arab Untuk Siswa Madrasah Ibtidaiyah Berbasis Android - Waeisul Bismi; Musriatun Napiah; Jordy Lasmana Putra; Fajar Shidiq (Computer Science (CO-SCIENCE), 2021)
With the increasingly open mindset of society today, especially Indonesia, it makes it easy for us to accept new things and implement them in our lives, these new things appear in many aspects such as one of which is education. In terms of education, it is better if it is carried out at an early age, especially in terms of learning a second foreign language or a foreign language substituting for English, this is what elementary school teachers have realized and has begun to be implemented recently, to do this elementary schools need tools to create methods. this learning becomes effective. Therefore the authors make an Arabic learning application that will make it easier for elementary school teachers to effectively introduce basic Arabic such as the recognition of the names of the day for elementary school children, which is equipped with sounds and images that can attract children's interests. This application can be run on an Android smartphone with a minimum Android OS 5.0 (Lollipop) and a maximum Android OS is 8.1 (Oreo).